IMPLEMENTASI METODE MIND MAPPING PADA PEMBELAJARAN AL-QURAN HADIST MATERI TAJWID DI SMPIT AS-SALAM MALANG - Handini Eka Putri; Dwi Fitri Wiyono; Fita Mustafida (VICRATINA, 2022)
SMPIT AS-SALAM Malang is one of the educational institutions at the secondary level that combines general education with religion. In learning Al-Qur'an Hadith, especially in class VII, the teacher has implemented various learning methods that aim to activate the student learning atmosphere. One method that can increase student creativity is the mind mapping method. Through the mind mapping method, it is hoped that the learning atmosphere will not be boring, because the learning system is not focused only on the teacher telling stories, but students who are more active and the teacher only as a facilitator, by using mind mapping the time used for taking notes is shorter, interesting, and fun. . When researchers make observations during learning in the classroom when the teacher uses the lecture method in learning. Students seem to be playing alone and less enthusiastic in participating in learning. The lesson looks boring because students only hear the teacher's explanation, students are also difficult to catch and understand quite a lot of recitation material.